HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU DAN KELENTUKAN PINGGANG DENGAN HASIL TOLAK PELURU PADA SISWA KELAS 10 SMA IT AL-ITTIHAD - Friarcha, Adly; Slamet, Slamet; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the observation and information gained from some teachers, that the students' shot put skills at SMA IT Al-Ittihad were still low. The problem of the low skills to do the shot put is including unhealty physical conditions because the shot put sport is a sport that requires physical conditions. The objective of this study was to determine the correlation between the explosive power of the arm and shoulder muscles and the flexibility of the waist with the shot put results at the tenth grade students of SMA IT-Al-Ittihad. The population of this study were the male students at the tenth grade of SMA IT Al-Ittihad contained 20 people. Because the total population was less than 100 people, the entire population was sampled (total sampling) as many as 20 people. The instruments of this study were two hand medicines: ball put used to determine the explosive power of the arm and shoulder muscles, and sit and reach used to determine the flexibility of the waist and the shot put results. The data obtained were analyzed using the correlation. Based on the results of study and data processing using statistical research procedures, it can be concluded that the relationship between variable X and variable Y was obtained rcount = 0.754> rtable = 0.456, so there was a relationship between variable X and variable Y. Thus, Ha was accepted. The conclusion of the hypothesis was accepted at the level Î± = 0.05, in other words, there was a significant relationship between the explosive power of the arm and shoulder muscles and the flexibility of the waist at the tenth grade students of SMA IT Al-Ittihad.Key Words: The Explosive Power of the Arm and Shoulder Muscles, The Flexibility of the Waist Muscles, The Shot Put Results